Role of social media information quality, social media usage frequency, and social media political marketing activities in increasing trust and political engagement among Gen Z women - Saputri, Arini; Hamid, Rahmad Solling; Dewintari, Putri (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study examines the role of social media information quality, social media usage frequency, and political marketing activities through social media in increasing the trust and political engagement of women in North Luwu. Methodology: A quantitative approach was used, with a population of female activists in the region. Data were collected from 250 respondents through an online survey and analyzed using a structural equation modeling approach based on partial least squares (PLS-SEM). Results and Findings: The results indicate that social media information quality has a significant and positive effect on trust (p < 0.05) but is not significant for political engagement (p > 0.05). Conversely, social media usage frequency has a significant and positive effect on both trust (p < 0.05) and political engagement (p < 0.05). Political marketing activities on social media significantly affect trust (p < 0.05) but do not show a direct significant effect on political engagement (p > 0.05). Trust is proven to mediate the relationship and has a significant effect on increasing political engagement (p < 0.05). Novelty and Originality: This study offers a new way of thinking about things by adding an important factor—the amount of time people spend on social media—that hasn't been looked at in previous studies (Hamid et al., 2020).Conclusion: This study helps politicians and political marketing consultants in the real world, and it also expands the ways that social exchange theory and relationship marketing can be used to understand women's political participation.Type of Paper: Research Article.